Dentoskeletal effects of Class II malocclusion treatment with the Twin Block appliance in a Brazilian sample: A prospective study - Luciano Zilio Saikoski; Rodrigo Hermont Cançado; Fabrício Pinelli Valarelli; Karina Maria Salvatore de Freitas (Dental Press Editora, 2014)
OBJECTIVE: The aim of this study was to assess the dentoskeletal effects of Class II malocclusion treatment performed with the Twin Block appliance. METHODS: The experimental group comprised 20 individuals with initial mean age of 11.76 years and was treated for a period of 1.13 years. The control group comprised 25 individuals with initial mean age of 11.39 years and a follow-up period of 1.07 years. Lateral cephalograms were taken at treatment onset and completion to assess treatment outcomes. Intergroup comparison was performed by means of the chi-square and independent t tests. RESULTS: The Twin Block appliance did not show significant effects on the maxillary component. The mandibular component showed a statistically significant increase in the effective mandibular length (Co-Gn) and significant improvement in the maxillomandibular relationship. The maxillary and mandibular dentoalveolar components presented a significant inclination of anterior teeth in both arches. The maxillary incisors were lingually tipped and retruded, while the mandibular incisors were labially tipped and protruded. CONCLUSIONS: The Twin Block appliance has great effectiveness for correction of skeletal Class II malocclusion in individuals with growth potential. Most changes are of dentoalveolar nature with a large component of tooth inclination associated with a significant skeletal effect on the mandible.